Azacitidine frontline therapy for unfit acute myeloid leukemia patients: Clinical use and outcome prediction. Issue 3 (March 2015) - Ramos, F.; Thépot, S.; Pleyer, L.; Maurillo, L.; Itzykson, R.; Bargay, J.; Stauder, R.; Venditti, A.; Seegers, V.; Martínez-Robles, V.; Burgstaller, S.; Récher, C.; et al.
Highlights European ALMA score (E-ALMA) takes into consideration ECOG, WBC and cytogenetics. It may be used in unfit WHO-defined AML patients treated frontline with azacitidine. Its design involved 371 unfit AML patients treated in 4 European countries. AZA may be a good choice for patients with a favorable or intermediate E-ALMA score.